Additions to the dragonfly genus Lauromacromia, with description of the female of Lauromacromia luismoojeni and new distributional records (Odonata: Corduliidae s.l.). Issue 2 (2nd April 2020) - Ehlert, Juliana; Parise Pinto, Ângelo
Abstract : Taxonomic, morphological and distributional data on three species of the rare South American corduliid genus Lauromacromia Geijskes, 1970 are updated based on specimens collected recently and old specimens deposited in natural history collections. The female of the poorly known Lauromacromia luismoojeni (Santos, 1967), an endemic species from the Brazilian Cerrado, is illustrated, described and diagnosed for the first time, based on a single specimen from the municipality of Mineiros, state of Goiás. This species was previously known from two males from two different localities: the original description from Distrito Federal, and an additional record from the state of Mato Grosso do Sul. New state records to Brazil are given for L. dubitalis (Fraser, 1939) (Amazonia domain of the state of Amapá), L. luismojenni (Cerrado domain of the state of Goiás), and for L. picinguaba Carvalho et al., 2004 (Atlantic Forest domain of the state of Paraná). Finally, the current knowledge about the genus is discussed.